Legal Vacuum in the Establishment of Positive Fictitious Administrative Decisions in Indonesia after the Job Creation Law - Siti Anisa Fatmawati; Tunggul Anshari Setia Negara; Shinta Hadiyantina (International Journal of Business, Law, and Education, 2026)
Article 175 of the Job Creation Law abolished the mechanism for submitting applications concerning positive fictitious administrative decisions to the State Administrative Court (PTUN) and delegated further regulation to a Presidential Regulation. However, the Presidential Regulation has not yet been issued, creating a normative vacuum regarding the procedures, form, evidentiary mechanisms, and validation of such decisions. This study examines the nature of this normative vacuum, its implications for legal certainty in public administration, and the design of an ideal regulatory framework. Using a normative legal research method with statutory, conceptual, and case approaches, legal materials were collected through library research and analyzed qualitatively. The findings show that the absence of the Presidential Regulation has led to legal uncertainty, inconsistent PTUN decisions, and inadequate protection of citizens’ administrative rights. Therefore, a clear regulatory framework is needed to govern the determination of positive fictitious administrative decisions, establish a formal legal instrument as evidence of such decisions, and strengthen judicial oversight to ensure legal certainty and effective legal protection.